(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In this paper an efficient algorithm using multi-frequency approach has been applied to fault diagnosis of analog electronic circuits using Pole Sensitivity analysis. In this paper, after application of the multi frequency approach to the pole sensitivity analysis the results show that the fault diagnosis of the circuit has increased. This has been proved by taking two circuits a second order Sallen Key Filter and RC Ladder network.